2020
DOI: 10.3390/rs12223768
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Model Calibration with Streamflow and Remote Sensing Based Evapotranspiration Data in a Data Poor Basin

Abstract: Conventional calibration methods adopted in hydrological modelling are based on streamflow data measured at certain river sections. However, streamflow measurements are usually sparse and, in such instances, remote-sensing-based products may be used as an additional dataset(s) in hydrological model calibration. This study compares two main calibration approaches: (a) single variable calibration with streamflow and evapotranspiration separately, and (b) multi-variable calibration with both variables together. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 71 publications
5
23
0
Order By: Relevance
“…The differences in the sensitivity of the parameters are due to different data used in the calibration process. Similar outcomes were obtained by Sirisena et al [16] and Moriasi et al [49]. Sirisena et al [16] concluded that the most sensitive parameters for evapotranspiration were connected to soil properties.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The differences in the sensitivity of the parameters are due to different data used in the calibration process. Similar outcomes were obtained by Sirisena et al [16] and Moriasi et al [49]. Sirisena et al [16] concluded that the most sensitive parameters for evapotranspiration were connected to soil properties.…”
Section: Discussionsupporting
confidence: 76%
“…Similar outcomes were obtained by Sirisena et al [16] and Moriasi et al [49]. Sirisena et al [16] concluded that the most sensitive parameters for evapotranspiration were connected to soil properties. Moriasi et al [49] pointed out that the high sensitivity of the soil parameters to AET indicated a connection between actual evaporation and soil water.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations